Transformation of Generation Z's consumption behavior in the digital ecosystem: A theoretical review of social media-based marketing strategies - Dewantoro, Riy; Sariani, Sariani; Suriono, Hadi (Priviet Social Sciences Journal, 2025)
This study aims to examine the transformation of consumption behavior among Generation Z in Indonesia within the context of the digital ecosystem, focusing on how social media shapes consumption patterns and influences marketing strategies adopted by businesses. This transformation reflects a shift from conventional consumption patterns rooted in functional needs toward more emotional, symbolic, and digitally-driven behaviors. Employing a qualitative descriptive approach through literature review, data were collected from various secondary sources, including scholarly journals, books, and recent research reports. The findings indicate that social media particularly influencer content and visual trends on platforms such as Instagram, TikTok, and YouTube plays a dominant role in shaping self-image and consumption preferences among Generation Z. Impulsive buying behavior is driven by e-commerce promotions, fear of missing out (FOMO), and peer pressure within digital communities. The ease of transactions via digital wallets, instant promotions, and seamless access to diverse products further reinforces a fast and instant consumption pattern. Unfortunately, this trend is not yet balanced by adequate financial literacy. These findings provide a crucial foundation for developing more personalized, interactive, and educational social media marketing strategies, while also supporting the enhancement of financial literacy among Generation Z, who are navigating an ever-evolving digital era.